A New Technique of Eliminating the Actual Plasma Background When Calibrating Emission Spectrometers with a CCD Recording System - Aleksandr S. Mustafaev; Anna N. Popova; Vladimir S. Sukhomlinov (Applied Sciences, 2022)
This research focuses on the development of a new technique of emission spectral analysis designed to accurately account for the background radiation. The technique enables the evaluation of background radiation while being unaffected by its spectral shape. This is possible through the use of standard data obtained in an analytical-line-recording process performed by light-intensity-to-electric-signal converters such as CCDs, PMTs, photodiodes, etc. This technique, when applied at a set RMS deviation of the analytical-line-radiation intensity, reduces the random error of a determined low impure-element concentration due to the optimal calibration-line slope. In areas of high concentrations, an accurate accounting of the background does little to affect the emission spectrometer’s measurement accuracy. This technique also allows the replication of calibration curves in spectrometers of the same type by a linear-intensity conversion with only two standard samples required. The technique was tested on SPAS-02 and SPAS-05 commercial spark spectrometers. The testing fully confirmed the aforementioned advantages of the developed technique. The authors also determined the applicability conditions of the conventional emission-spectrometer-recalibration method by a linear conversion of the analytical-line intensity.